Insights into Economics and Management Vol. 13 - Dr. James E. Curtis, Jr. (Insights into Economics and Management Vol. 13, 2021)
Researchers have a long-standing interest in understanding the causes and consequences of inequality. One approach to analyzing inequality is to compare average economic choices from a classical theoretical framework. Another approach considers the impact of the formation of society, through statutes and institutions, on average economic outcomes. James Curtis Jr uses applied econometrics, applied labor economics, applied theory and empirical data to provide results that we cannot reject the existence of a negatively bounded correlation between the duration of time from zero wage labor constraints and the magnitude of unexplained differences in wealth. Furthermore, James Curtis Jr promotes a concept of entrepreneurial education in economics.